Rational structures on multiple zeta values - Keilthy, A (2020)
Motivated originally by the question of defining a rational canonical associator, we study rational structures associated to multiple zeta values. In particular, we focus on the question of providing an explicit description of the motivic Lie algebra associated to the projective line minus three points via new families of motivic relations among multiple zeta values.